Studi Tingkat Literasi Keuangan dan Perilaku Konsumtif Mahasiswa serta Pengaruhnya terhadap Pengelolaan Keuangan Pribadi - Rosyia Wardani; Sofiati Wardah; Rusdi; Syaiful Amri (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2025)
This study examines the influence of financial literacy and consumptive behavior on the personal financial management of students at STIE AMM Mataram. Using a quantitative causal-associative approach, the research surveyed 151 respondents selected from a population of 242 students through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression. The results show that financial literacy does not have a significant effect on personal financial management, indicating that students' financial knowledge has not been fully translated into daily financial practices. Conversely, consumptive behavior has a significant and dominant influence, demonstrating that lifestyle-driven spending, peer pressure, and digital financial access strongly shape students’ financial habits. Simultaneously, financial literacy and consumptive behavior significantly affect personal financial management, with a combined contribution of 57.5%. These findings highlight that students’ financial management challenges are more behavioral than cognitive, emphasizing the need for practical financial education, stronger self-control, and awareness of digital financial risks. The study implies that higher education institutions should develop programs focusing on budgeting skills, digital finance awareness, and responsible consumption to improve students' financial well-being.